2016
DOI: 10.4103/0976-9668.175078
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and knowledge toward mobile-health among the college going students in Coastal South India

Abstract: Background:Among the manifold uses of mobile phones, mobile-health (mHealth) has been an important one, which is the practice of public health initiatives by awareness raising and communication campaigns. Optimum utilization of mHealth is possible only through adequate awareness. Hence, we aimed to study the perceptions and knowledge about mHealth among college going students in Mangalore, India.Materials and Methods:A cross-sectional study was conducted in March 2014 among 627 students in selected engineering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…This study was conducted among students studying in non-professional courses in Delhi University and most of them were in the age group of less than 22 years which is comparable to the study on mHealth by Parthaje et al in South India among students studying in professional courses in which more than 60% of the students were in the age group of ≤20 years. 10 Students staying off campus in the current study (64%) matches with a study by Peprah et al in Ghana among University students which shows almost 60% of the students were day scholars. 11 Majority of the study participants were satisfied with the mHealth approach which doesn't interfere in their routine activities and is in line with the findings by Loo about acceptance of healthcare services on mobile phones in which the consumers are interested in using mHealth services and satisfied with this approach as well to a another study conducted in South India where the participants have a positive perception towards mHealth.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study was conducted among students studying in non-professional courses in Delhi University and most of them were in the age group of less than 22 years which is comparable to the study on mHealth by Parthaje et al in South India among students studying in professional courses in which more than 60% of the students were in the age group of ≤20 years. 10 Students staying off campus in the current study (64%) matches with a study by Peprah et al in Ghana among University students which shows almost 60% of the students were day scholars. 11 Majority of the study participants were satisfied with the mHealth approach which doesn't interfere in their routine activities and is in line with the findings by Loo about acceptance of healthcare services on mobile phones in which the consumers are interested in using mHealth services and satisfied with this approach as well to a another study conducted in South India where the participants have a positive perception towards mHealth.…”
Section: Discussionsupporting
confidence: 90%
“…11 Majority of the study participants were satisfied with the mHealth approach which doesn't interfere in their routine activities and is in line with the findings by Loo about acceptance of healthcare services on mobile phones in which the consumers are interested in using mHealth services and satisfied with this approach as well to a another study conducted in South India where the participants have a positive perception towards mHealth. 10,12 A study by Jain et al found that young individuals are more interested in using mobile apps for health related behaviour change which supports our study finding of young college students satisfaction level in using mHealth for lifestyle and behaviour change. 8 While trying to find out the association of the study participants socio-demographic characters (age, course and residence) with their view about the use of mHealth technology as a health promotion tool in India none of the variables were significantly associated with the satisfaction, sharing of messages and rating of mHealth as p>0.05 in all the factors analyzed (Table 3).…”
Section: Discussionsupporting
confidence: 87%
“…The stakeholders in the study are the students and professionals of technical and medical disciplines (n 5 386), general populations including doctors (n 5 409) and health software developers (n 5 17). In both cases, the questionnaire was prepared based on the published articles (Kayyali et al, 2017;Khatun et al, 2014;Atulomah et al, 2010;Parthaje et al, 2016;Ehteshami et al, 2013;Dutta-Bergman, 2004;Davis, 1989;Rai et al, 2013;Venkatesh and Davis, 2000;Defense Acquisition University, 2020;Ryan and Raducha-Grace, 2009). The data were collected from questionnaire survey (online and offline sources) and interviews with software developers.…”
Section: Sample Sizesmentioning
confidence: 99%
“…Many research studies have been carried out in this domain and across the regions of India. Along the patients’ use-phases, the study included the development of specific mHealth applications or features for creating awareness (AWR) about health and diseases (Parthaje et al , 2016; DeSouza et al , 2014), interventions (Shet et al , 2010; Singh et al , 2018; Bali and Singh, 2007; Praveen et al , 2014) and reminders (Venkat, 2016; NHRM, 2019), diagnosis (Salve et al , 2012; Rangaswamy Thara, 2013; Bhargava et al , 2018) and treatment (Shet et al , 2014; Chandra et al , 2018). This would help healthcare professionals in providing healthcare access and continuous monitoring services to the people living in the low resource setting areas.…”
Section: Introductionmentioning
confidence: 99%